De tempos em tempos a terra treme - Almeida, Tarcisio (2017)
The following research proposes an intermediation between the collection of artworks by the artist Zofir Brasil (located in the city of Rio de Contas BR) and the modes of subjectivation within the community in which it is inscribed. Throughout the work we investigate, using different devices, the fields of affectability proposed by the artist, his artistic interventions and the sensitive communities generated by his propositions. In this way, we consider the artistic experience as a mediator of worlds and navigate through its passages adopting multiple historical, anthropological, philosophical and artistic perspectives as the compositional strategy of its cartographies